EFFECTIVENESS SERVICE INFORMATION TO INCREASE CONCEPTION X'SELF STUDENT of SMA COUNTRY 1 ANGKOLA WEST - VITRIA LARSEMAN DELA (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This research is based of problems still lower him conception student x'self. Target of Research is to To know information service efektifitas in improving student x'self concept [pass/through] information service. Research method the used is research of True Experimental Design with Pretest-Posttest Control Group Design. With experiment class sampel that is XI IPS 1 counted 20 control and student that is class of XI IPS 2 counted 20 student so that the amount of sampel 40 student. Information service done/conducted by the three of times;rill, namely in first meeting execute pretest, second conducting information service bemberian and third conduct posttest. This data in analysis by using formula of wilcoxon ranks signed test and Z smirnov kolmogorov constructively SPSS version 20.00.Hasil finding [at] experiment group and group control there are make-up of which is deliverance signifikan result of pretest control and experiment posttest. Variable mean conception student x'self equal to 62.9000. ( Eksperimen postteste) while class control 60.3000. ( control posttest) this seen very difference of signifikan.Kesimpulan of this research Result of data processing, indicating that pelaksannaa of information service can improve class student x'self concept of XI IPS SMA Country 1 ANGKOLA WEST Keyword: Service Information and Concept X'Self